Genomic characterization and transcription analysis of European sea bass (Dicentrarchus labrax) rtp3 genes. - Moreno, Patricia; Gémez-Mata, Juan; Álvarez-Torres, Daniel; García-Rosado, Esther; Béjar-Alvarado, Julia; Alonso-Sánchez, María del Carmen (Elsevier, 2023)
Fish RTP3, belonging to the receptor-transporting protein family, display several functions, including a putative antiviral role as virus-responsive gene. In this work, we have identified and characterized two different European sea bass rtp3 genes. In addition, an in vivo transcription analysis in response to LPS, poly I:C and betanodavirus infection (RGNNV genotype) has been performed. The sequence analysis showed that European sea bass displays two rtp3 genes, X1 and X2, composed of two exons and a single intron (1007-bp and 888-bp long, respectively), located within the ORF sequence. The full-length cDNA is 1969 bp for rtp3 X1, and 1491 bp for rtp3 X2. Several ATTTA motifs have been found in the intron sequence of both genes, whereas rtp3 X1 also contains this motif in both untranslated regions. The transcription analyses revealed significant level of rtp3 X2 mRNA in brain and head kidney after LPS and poly I:C inoculation; however, the induction elicited by RGNNV infection was much higher, suggesting an essential role for this protein in controlling NNV infections
Keywords: Agentes antivíricos; Lubinas - Genética; Lubinas - Inmunología; Peces - Inmunología; rtp3; European sea bass; LPS; Poly I:C; RGNNV